ARCHAEOLOGICAL RESEARCH ON THE TERRITORY OF THE ZNAMENSKAYA CHURCH IN KHASAVYURT - Guguev, Urij Konstantinovic; Tajmazov, Artur Israpilovic; Abiev, Askerhan Kamalovic (History, Archeology and Ethnography of the Caucasus, 2019)
The article is devoted to the results of exploratory archaeological research on the territory of the Znamenskaya Church in Khasavyurt. To identify and explore the cultural layers we created three test pit a total area of 12 sq. m. Archaeological research revealed the presence in this territory of late cultural layers. Inside the Church (pits # 2 and # 3) they belong to two stratigraphic periods. Chronologically, the first period lasted from the time of the construction of the temple in 1902-1907 gg. before the fire of 1943, the Second period covers the time from the fire of 1943 to the present (beginning of 2000-ies?). In the cultural strata outside the Church (pit No. 1) the fire was not reflected. They also belong to two chronological periods, but one of them covers the time of construction of the temple (1902-1907), and the second – the time of its operation up to the present. Neither inside nor outside the Church studies have revealed any cultural layers and remains prior to the time of its construction.